The Jewish Sign Prophets -A.D. 40–70 Their Intentions and Origin: 1. THE JEWISH SIGN PROPHETS - Barnett, P. W. (New Testament studies, 1981)
As we read those parts of Josephus'1 works which coincide with the Apostolic Age (in round figures A.D. 30–70) we encounter a number of references to certain prophetic figures. In the absence of existing descriptive titles we will refer to them as the Jewish Sign Prophets.